Pengambilan Keputusan Mahasiswa Non Muslim Untuk Studi di Perguruan Tinggi Islam - Kurnianto, Hadi, Taufik Kasturi, M.Si., Ph.D (2016)
The purpose of this study was to uncover and find out the decision-making non-Muslim students to study at Islamic universities Sampling was done by purposive sampling. The number of informants in this study are four informants, comprising 3 males and 1 female characteristics: non-Muslim students studying high diperguruan Islam. This study uses a qualitative method of data collection using interviews and observations, and analyzed descriptively. The results showed that 1. Decision starting from identification of the problem is choosing one of the various alternatives 2. Consider the options and look for information 3. Convinced that the decision has been taken that the future will be better to make changes 4. Having desired goals and expectations 5. revealed several factors that influence the decision-making non-Muslim students to study Islamic high diperguruan include motivation, the image of the college and the elderly.